HOSPITAL TRANSFERS: PERSPECTIVES OF NURSING HOME RESIDENTS AND NURSES. (20th December 2022) - Ahmetovic, Alma; Drucker, Claire; Huber, Lesa; Unroe, Kathleen; Hickman, Susan
Abstract: Between 1 million and 2.2 million nursing home residents are transferred to a hospital emergency department each year. These transfers are costly, have negative health outcomes, and can increase the morbidity and mortality of residents. The purpose of this study was to examine the transfer process between the nursing home and the hospital from the perspective of nursing home residents and nurses, focusing on how decisions were made to transfer residents. Using a qualitative descriptive method, 22 participants were recruited from four nursing homes located in rural Indiana. Purposive sampling, semi-structured interviews, and conventional content analysis were used to collect and analyze narratives obtained from residents and nurses about their experiences with a recent transfer. The participants described four aspects of the transfer process: transfer decisions, transport experiences, hospital stays, and returns to the nursing home. The most common reason for transfers was an acute exacerbation of a chronic condition, and the decision to transfer was often made by a nurse. Most residents found aspects of the transfer aversive or upsetting. The return to the nursing home was typically welcomed but often challenging due to problems with mobility, medications, and cognitive changes. Participants also provided several recommendations for avoiding potentially preventable transfers including adding "in-house" diagnostic testing and treatment equipment, improving staff competencies in managing acute exacerbations, increasing staffing, improving communication among staff, and increasing staff familiarity with resident histories and preferences. The findings have several clinical and policy implications for preventing or decreasing the negative effects of hospital transfers.